Social equity, inclusiveness, gender, and climate change adaptation: Helping people and communities build climate resilience (A compilation of article abstract) - Soriaga, Rowena; Cabriole, Marie Aislinn; Marie, Aislinn; Oro-Monville, Emilita; Hellin, Jon (2024)
Smallholder farmers, particularly women and the poor, are disproportionately affected by the climate crisis and require timely, adequate adaptation solutions to mitigate its impacts. Delayed or ineffective adaptation efforts can exacerbate their vulnerability. To address these challenges, the CGIAR Initiative on Climate Resilience (ClimBeR) promotes science-based innovations aimed at transforming the climate adaptation capacity of food, land, and water systems in six countries: Guatemala, Kenya, Morocco, the Philippines, Senegal, and Zambia. ClimBeR's goal is to enhance smallholder resilience while ensuring equitable outcomes and contributing to poverty reduction.